2018
DOI: 10.2196/resprot.8936
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Impact of Hearing Aid Use and Auditory Training on Cognition, Depressive Symptoms, and Social Interaction in Adults With Hearing Loss: Protocol for a Crossover Trial

Abstract: BackgroundSensorineural hearing loss is the most common sensory deficit among older adults. Some of the psychosocial consequences of this condition include difficulty in understanding speech, depression, and social isolation. Studies have shown that older adults with hearing loss show some age-related cognitive decline. Hearing aids have been proven as successful interventions to alleviate sensorineural hearing loss. In addition to hearing aid use, the positive effects of auditory training—formal listening act… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 59 publications
0
3
0
3
Order By: Relevance
“…Participants were recruited from eight independent living retirement facilities and surrounding communities across Melbourne, Australia. The complete study protocol is described elsewhere 15…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Participants were recruited from eight independent living retirement facilities and surrounding communities across Melbourne, Australia. The complete study protocol is described elsewhere 15…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Measures of cognition are therefore relevant to understanding the processing and individual expression of listening and communication (Lunner et al, 2009). For example, a recent study using a hearing-impairment simulation demonstrated that hearing loss does indeed impact cognitive-test performance, and this is not only due to reduced audibility (Füllgrabe, 2020).The studies identified in this review used measures of cognition for a variety of purposes: (1) to understand relationships between cognitive domains and listening (Amichetti et al, 2013;Ferguson and Henshaw, 2015;Keidser et al, 2016); (2) to account for variance in listening ability that is not identified within standard audiological measures (Kronenberger et al, 2014;Kaandorp et al, 2017;Moberly et al, 2018b); (3) as an indicator of neurocognitive function (Gates et al, 2008;Wong et al, 2014;Dawes et al, 2015); and (4) to determine if targetting cognition assists with rehabilitation (Pichora-Fuller and Levitt, 2012;Castiglione et al, 2016;Nkyekyer et al, 2018). As with language and communication, measurement of cognition as a separate and discrete function is complex.…”
Section: Cognitive Assessment Measuresmentioning
confidence: 99%
“…Использование слуховых тренировок у пациентов, носящих СА, повышает адаптацию пациента к среде, стабилизирует его когнитивный и эмоциональный статус. Так, в Австралии было проведено исследование [2,5,6] 40 пациентов с ХСНТ в возрасте от 50 до 90 лет с симметричной билатеральной потерей слуха умеренной и выраженной степени, использующих СА не менее 3 месяцев. Проводилась оценка уровня депрессии с Н а у к а и и н н о в а ц и и в м е д и ц и н е Т.5(1)/2020 E N T d i s e a s e s 14.01.03 Болезни уха, горла и носа (медицинские науки) помощью гериатрической шкалы депрессии и когнитивной функции до и после проведения слухового тренинга в течение 6 месяцев.…”
Section: результаты и их обсуждениеunclassified